SURFUCE STRUCTURE DAN DEEP STRUCTURE MAKNA QIRADAH: Analisis Teori Noam Chomsky Terhadap QS. Al-Baqarah: 65 - Asy'ary Asy'ary (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This research explores the concepts of deep structure and surface structure in the context of the interpretation of the word “qiradah” based on the analysis of Noam Chomsky's theory on Surah Al-Baqarah 65. Chomsky, a linguistic expert, developed the transformative-generative theory, providing a profound understanding of language. In this theory, Chomsky emphasizes that language consists of the surface structure, which is the visible part of language, and the deep structure, which is the core meaning of language. The author employs a qualitative method, reviewing relevant prior works for this discussion. The aim is to validate the applicability of Noam Chomsky's linguistic theory in understanding language. The study reveals that language indeed has both surface and deep structures, particularly in the interpretation of the word “qiradah” in Surah Al-Baqarah 65. The surface structure signifies the physical transformation into apes that happened to the Children of Israel, while the deep structure or core meaning indicated by the word “qiradah” is the transformation of the heart and behavior resembling apes, not the physical change itself.